Short Communication: Muscle protein bands resolved by Sarotherodon melanotheron from fresh and brackish water habitats - R.N. OLADOSU-AJAYI; I.T. OMONIYI; H.E. DIENYE (Smujo International, 2018)
Oladosu-Ajayi RN, Omoniyi IT, Dienye HE. 2018. Muscle protein bands resolved by Sarotherodon melanotheron from fresh and brackish water habitats. Nusantara Bioscience 10: 40-45. An electrophoretic analysis of muscle protein of Sarotherodon melanotheron from freshwater (Eleiyele Reservoir, Ibadan, Nigeria) and brackish water (Lekki Lagoon, Lagos, Nigeria) was carried out using the Sodium Dodecyl Sulphate Polyacrylamide Gel Electrophoresis (SDS-PAGE). The protein banding patterns for the fish species were distinguishable. The freshwater S. melanotheron samples displayed 15-22 protein bands with the male samples having the highest while the brackish water S. melanotheron samples displayed 13-20 protein bands with the female having the highest. The freshwater S. melanotheron were also observed to have resolved a higher range of protein bands of molecular weights ranging between 20 kd to 99 kd than the brackish water species, which resolved protein bands of lower molecular weights ranging between 20 kd to 95 kd. The electrophoretic analysis of muscle proteins revealed that SDS-PAGE can be considered a good taxonomic criterion to differentiate among and within fish species.